2009
DOI: 10.1089/thy.2008.0400
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Effect of Furosemide on Radioiodine Urinary Excretion in Patients with Differentiated Thyroid Carcinomas Treated with Iodine 131

Abstract: Our results demonstrated that furosemide given as an adjuvant medication in patients with DTC causes a significant decrease in urinary excretion of radioiodine and its higher blood concentration. Therefore, furosemide should not be recommended as an adjuvant therapy to radioiodine ablation in patients with DTC previously iodine depleted by low-iodine diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
0
15
0
2
Order By: Relevance
“…However, Matovic et al [13] recently reported that blood radioactivity was greater in patients who received furosemide than in controls, even though the patients who received furosemide passed larger volumes of urine. The mechanism responsible for this paradoxical effect is unknown.…”
Section: Discussionmentioning
confidence: 98%
“…However, Matovic et al [13] recently reported that blood radioactivity was greater in patients who received furosemide than in controls, even though the patients who received furosemide passed larger volumes of urine. The mechanism responsible for this paradoxical effect is unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Outcome studies on this approach are unavailable, and the half-life of thyroxine, about 7 d in a euthyroid patient, makes this recommendation of uncertain value. The use of a diuretic to reduce body iodine content is not advised because of the side effects of hypokalemia and hypotension and because furosemide causes a decrease in urinary iodide excretion and higher blood concentration (63).…”
Section: Follow-upmentioning
confidence: 99%
“…Some of them point to the fact that this diuretic influences the acceleration of iodine urinary excretion leading to iodine depletion. However, in one of our previous studies (Matovic et al, 2009a) it has been unmistakably shown that this diuretic, in combination with low iodine diet, slows down the elimination of radioiodine in patients treated with this radionuclide (figure 1. and figure 2. ).…”
Section: Furosemidementioning
confidence: 98%
“…Some researches have shown that the effects of low iodine diet can include an increased iodine retention, instead of iodine depletion, especially if it is combined with the application of diuretics (Hamburger, 1969;Norfray & Quinn, 1974;Tepmongkol, 2002, Matovic et al 2009a). …”
Section: Low Iodine Dietmentioning
confidence: 99%